Sustaining Islamic School Reputation: The Multidimensional Role of Educational Public Relations - Mohammad Bilutfikal Khofi; Suheri Suheri; Miftahus Salam; Krisna Wijaya; Ahmad Mu'is (Jurnal Inovatif Manajemen Pendidikan Islam, 2026)
In the competitive landscape of Islamic education, maintaining a positive reputation is crucial for Islamic schools to attract public trust and ensure sustainability. Effective educational public relations (PR) plays a central role in addressing modern communication challenges while upholding Islamic values. This study focuses on MA Atqia Bondowoso, exploring how a multidimensional PR approach can sustain its reputation amidst the dynamics of the digital era. The research aims to develop a holistic PR framework that integrates branding, image building, reputation maintenance, effective communication, and community engagement. Employing a qualitative case study approach at MA Atqia Bondowoso, the study examines the role of PR in sustaining the school’s reputation. Data were collected through interviews, observations, and documentation, then analyzed inductively following Miles and Huberman’s stages. Data validity was ensured through triangulation and member checking to provide a comprehensive overview of PR strategies in maintaining the school’s reputation. The findings reveal that a strategic PR approach, combining digital and traditional communication channels, enhances public trust, strengthens school competitiveness, and ensures long-term sustainability. Key strategies include consistent branding, transparent communication, and active community engagement, aligned with Islamic principles. The study proposes a comprehensive PR model that addresses contemporary communication challenges while preserving Islamic values.